Promoting technological literacy through virtual game-based field trips: Effects on knowledge, attitudes, and gender - Phillip Bengel; Carina Peter (European Journal of Geography)
Virtual field trips in combination with digital game-based learning offer great potential for creating new learning environments, especially for geography education. Those approaches are not only needed to transfer knowledge but also to contribute to creating a more technologically literate society. For the future design of learning spaces and the corresponding professional development of teachers, it is indispensable to learn what the pedagogical advantages and limitations of fully virtual game-based approaches are. For this, it is necessary to know whether purely virtual concepts differ in knowledge transfer from those applied in technology-supported field trips on site. When it comes to promoting technological literacy, additional relevant questions are whether there are influences on participants’ attitudes toward modern technologies and whether there are implied gender effects in this regard. An empirical comparative study of a total of n=110 German high school students was conducted using a survey to answer these questions. Key results are that actual and virtual designs using technology-supported game-based learning approaches can be equally effective in knowledge transfer. Further certain technology-averse attitudes could be identified, which were more prevalent among females than males. This gender gap could be leveled out by the effects of the virtual game-based field trip. Across genders, the levels of aversion were reduced, as well, while affirmative attitudes toward modern technology rose.